Does Facebook activity reveal your dark side? Using online language features to understand an individual's dark triad and needs. Issue 2 (25th January 2022) - Yuan, Cuixin; Hong, Ying; Wu, Junjie
ABSTRACT: Language is a powerful indicator of psychological processes. This study analysed the language features on online social networks to understand individuals' Dark Triad personality and need for power. Results based on data from 130 individuals using the Linguistic Inquiry and Word Count (LIWC) dictionary showed that language features such as I-words, negative emotion, and clout were positively related to Machiavellianism, which was positively associated with the need for power. We also found indirect effects of Analytic, I-words, and Social words on the need for power through Narcissism and indirect effects of Analytic and Authenticity on the need for power through Psychopathy. In addition, gender moderated the relationship between I-words and Machiavellianism, in that the relationship was stronger for men than for women. Finally, we built a regression model using language features to predict individuals' Dark Triad and the need for power. Based on the findings, we put forward some suggestions for managers to recruit and promote appropriate employees.